The Relationship between the Implementation of Urine Foley Catheter Installation and the Occurrence of Urinary Tract Infections in Inpatients at Efarina Etaham Berastagi Hospital, Karo Regency - Tarigan, Sri Wahyuni (PT Inovasi Pratama Internasional, 2023)
Infection channel urinary tract (UTI) is infection caused by developing breed microorganisms inside channel urine, though consists from various liquids, salts and products waste, usually urine is not contain bacteria, viruses or microorganisms other. If bacteria going to biological urine or kidney and develop breed in the urine, it happens infection channel bladder (UTI). Design study This is descriptive with Cross sectional approach. Total sample obtained is 50 people. Done data analysis with using the chi-square test know connection implementation Foley catheter insertion with happening infection channel urinary. Result study is known as many as 25 of 31 people (80%) patients take care stay with proper placement of a foley urinary catheter No happen infection channel urinary tract, whereas 6 of 31 (20%) patients take care stay with proper placement of a foley urinary catheter experience infection channel urine. As many as 7 of 19 people (36%) patients take care stay with Incorrect placement of a foley urinary catheter Good No happen infection channel urinary tract, while 12 of 19 (64%) patients take care stay with Incorrect placement of a foley urinary catheter good experience infection channel urinary. Result analysis statistics show There is Connection Implementation Urine Foley Catheter Installation with Happening Infection Channel Urinary (p = 0.002). and OR value = 7.143.